HfO2-based resistive switching memory with CNTs electrode for high density storage. (June 2017) - Cheng, W.K.; Wang, F.; Han, Y.M.; Zhang, Z.C.; Zhao, J.S.; Zhang, K.L.
Graphical abstract: Highlights: CNTs are used as electrode in HfO2 -based RRAM devices for high density integration. The device displays self-compliance, forming-free behavior and LRS nonlinearity. The device switches successfully with the Ireset less than 130 nA. The resistive switching mechanism is discussed as well. Abstract: In this paper, the HfO2 -based resistive switching memory (RRAM) using carbon nanotubes (CNTs) as contact electrodes for high density integration is demonstrated. The Al/HfO2 /CNTs devices show self-compliance, forming-free and low resistive state (LRS) nonlinearity with less than 130 nA reset current (Ireset ). By contrast with the Al/HfO2 /Ti devices, resistive switching behavior has been enhanced significantly by using CNTs electrode. For the Al/HfO2 /CNTs devices, current–voltage (I-V) characteristics demonstrate that the current conduction in high resistive state (HRS) and low resistive state (LRS) is controlled by space-charge-limited current (SCLC) and trap-controlled SCLC mechanism, respectively.